Kesalahan Berbicara Bahasa Indonesia Oleh Mahasiswa Asing Penutur Bahasa Arab Dalam Membaca Cerita Legenda Nusantara di Universitas Jenderal Soedirman - Intan Sukma Melati; Uki Hares Yulianti; M. Riyanton (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to identify and analyze the forms and causes of phonological errors made by non-native Arabic-speaking students when reading the text of the Legend of Roro Jonggrang at Jenderal Soedirman University. One of the errors identified was a phonemic shift in the pronunciation of the word “candi” [candi], which was realized as “jandi” [jandi]. The change from /c/ to /j/ occurs because the Arabic phonology lacks the /c/ phoneme, while the closest sound is the (jīm) phoneme, which is realized as /j/. The absence of a direct phonetic equivalent prompts speakers to substitute a foreign phoneme, resulting in pronunciation that deviates from Indonesian language norms. The research method used is descriptive qualitative, with data from three students from Yemen. The data consists of the students’ spoken utterances, obtained through observation, interviews, audio recordings during text reading, and documentation. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Data validity was strengthened through source triangulation and member checking to ensure the research results remain objective and consistent with field facts. The research results indicate that there are three main types of phonological errors: phoneme addition (12 instances), phoneme deletion (25 instances), and phoneme substitution (57 instances). Based on these findings, it can be concluded that Arabic-speaking students still face challenges in adapting to the phonotactic patterns of the Indonesian language. This study is expected to contribute to a learning approach focused on strengthening articulation exercises for sound production, as well as intensive guidance that emphasizes empathetic pedagogical interaction between teachers and learners, so that foreign students’ pronunciation skills can develop in accordance with the phonological rules of the Indonesian language. Keywords: phonological errors, foreign speakers, Indonesian language learning, phonology.